2009
DOI: 10.1007/s00125-009-1481-x
|View full text |Cite
|
Sign up to set email alerts
|

Meat consumption and the risk of type 2 diabetes: a systematic review and meta-analysis of cohort studies

Abstract: Aims/hypothesis Diet is thought to play an important role in the aetiology of type 2 diabetes. Previous studies have found positive associations between meat consumption and the risk of type 2 diabetes, but the results have been inconsistent. We conducted a systematic review and meta-analysis of cohort studies of meat consumption and type 2 diabetes risk. Methods We searched several databases for cohort studies on meat consumption and type 2 diabetes risk, up to December 2008. Summary relative risks were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
209
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(244 citation statements)
references
References 65 publications
24
209
1
10
Order By: Relevance
“…The high levels of sodium and nitrate preservatives in processed meats may raise blood pressure, which may increase the risk of incident PAD (39). Meta-analyses have shown consistent and positive associations between meat and another risk factor for PAD, type 2 diabetes, as was found in this study (data not shown) (40). Additionally, intake of heme iron has been consistently associated with type 2 diabetes (34).…”
Section: Discussionsupporting
confidence: 70%
“…The high levels of sodium and nitrate preservatives in processed meats may raise blood pressure, which may increase the risk of incident PAD (39). Meta-analyses have shown consistent and positive associations between meat and another risk factor for PAD, type 2 diabetes, as was found in this study (data not shown) (40). Additionally, intake of heme iron has been consistently associated with type 2 diabetes (34).…”
Section: Discussionsupporting
confidence: 70%
“…In the review by Aune et al (12 cohort studies from the USA, Europe, Asia and Australia) [4], a statistically significant positive association between total red meat and processed meat and type 2 diabetes risk emerged (21% and 41% increased risk for highest vs lowest intake, respectively), while total meat consumption was not significantly associated. In the review by Micha et al (seven cohort studies from the USA, Germany and China) [5], a statistically significant positive association emerged between processed meat and the combination of processed and unprocessed red meat and risk of type 2 diabetes (19% and 12% increased risk for 50 and 100 g/day, respectively), which is well in agreement with our estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Three recent meta-analyses of prospective studies emphasised that a diet rich in red and processed meat consumption is an important and independent contributor to type 2 diabetes risk [4][5][6]. In these meta-analyses a large…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Our finding is in keeping with a meta-analysis of 12 cohort studies where consumption of processed and red meat associated with increased diabetes risk. 28 These findings raise concern about current promotions of high-protein diets for weight loss. 29 One strength of this study was its prospective cohort design, which minimized recall and selection biases.…”
Section: Discussionmentioning
confidence: 99%